Perlindungan Hukum Konsumen Atas Praktik Overclaim Iklan Produk Skincare di E-Commerce Dihubungkan dengan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Nina Andriani; Yuniar Rahmatiar; Muhamad Abas; Suyono Sanjaya (Universitas Batanghari Jambi, 2025)
Overclaim occurs when business actors convey excessive or factual information in product promotions, thus misleading consumers and violating the principles of transparency and honesty in trade. In the skincare industry on e-commerce platforms, this practice is increasingly widespread along with high market competition. Consumers are often disadvantaged because they do not have adequate ability to verify the truth of product claims. This study aims to examine the form of legal protection provided to consumers, as well as to examine the responsibilities of business actors based on the provisions of Law Number 8 of 1999 concerning Consumer Protection. The method used is qualitative with a normative legal approach, which focuses on literature studies and analysis of relevant laws and regulations. The findings in this study indicate the need to strengthen the legal protection system, both preventively through advertising monitoring mechanisms, and repressively through the application of strict legal sanctions. The active involvement of e-commerce platforms is also key to creating effective consumer protection in the digital space.